O-002 Presenting Diffusion-Restricted Core Volume, Not Time, Predicts Final Infarct Volume after Thrombectomy in Anterior Circulation Large Vessel Occlusion Stroke. (29th July 2016) - Cristiano, B; Pond, M; Basu, S; Oyoyo, U; Jacobson, J
Abstract : Purpose: With thrombectomy for anterior circulation large vessel occlusion (ACLVO) stroke, time to recanalization is considered important, but collateral status may be a more important driver of outcome than time. Here we used data from an institutional cohort to test the hypothesis that small DWI core volume on presenting MRI, a biomarker of robust collateral perfusion, is the dominant predictor of favorable outcome after thrombectomy. Methods: A cohort of 56 ACLVO patients treated with thrombectomy at our institution between 11/1/2012 and 5/15/2015 was studied by logistic regression using final infarct volume ≤50 mL, a validated predictor of good clinical outcome, as the outcome variable. The following univariate predictor variables were assessed: age, NIHSS score, time to CTA, time to CTA ≤ 6 hours, presenting diffusion-restricting core volume, presenting core ≤ 50 mL, time to recanalization, time to recanalization ≤6 hours, time to recanalization ≤8 hours, and recanalization ≥ TICI2B. Finally, multiple logistic regression models were created comparing time and presenting core as predictors adjusting for age and TICI2B recanalization status. Results: Of the univariate predictors studied, only presenting core volume, presenting core volume ≤50 mL, age, and post procedure TICI ≥ 2 B were significant predictors of the outcome variable at the α = 0.15 level (Table 1 ). Paradoxically, the administration of IV tPA was associated with larger core volumes in our dataset ( β = 1.53, p = 0.100). Of the time-based predictors, time to recanalization and time to recanalization ≤8 hours performed best, although none of them approached significance at the α = 0.15 level. The performances of time, core volume, age and TICI ≥ 2 B as predictors of small final infarct were then evaluated in a multiple logistic regression model. In that model, presenting core volume ≤50 mL, not time to recanalization, was the dominant predictor of small final infarct volume (OR 15.2 [95CI 1.3, 180] vs. 0.94 [95CI 0.78, 1.1]). Finally, a 3 variable logistic regression model incorporating presentation core volume, age, and TICI ≥ 2 B as covariates was constructed. The resulting model was statistically significant χ 2 (2) = 22.65, ( p < 0.001) and accounted for 52.9% of the variance in outcome with a percent accuracy of classification of 85.4%. Conclusion: Presentation volume of diffusion-restricted core was a strong predictor of final infarct volume post-thrombectomy in this cohort of ACLVO patients, whereas time-based covariates showed little if any significant predictive value. For every 1 mL increase in presentation infarct volume, the odds of a small completed infarct were reduced by about 6%. A presentation core volume ≤50 mL improved the odds of a small final infarct by at least 26%, probably more. Disclosures: B. Cristiano: None. M. Pond: None. S. Basu: None. U. Oyoyo: None. J. Jacobson: 4; C; GeneLux.